Microwave-Assisted Pyrolysis Of Biomass For Bio-Oil And Bio Char Production - Yip, Chee Yang (Universiti Malaysia Sarawak (UNIMAS), 2018)
Microwave-assisted pyrolysis is an alternative technique of conventional heating which undergo thermochemical process to convert biomass become bio oil, bio char and biogas. Microwave pyrolysis is more rapid and efficient to produce product compared to conventional heating. This study focuses on develop microwave-assisted pyrolysis to convert biomass become bio oil and bio char. A modified household microwave with 800 W was used to pyrolyze Moringa seed and Karanja to become bio oil and bio char. This experiment was repeated in different parameters for example time, temperature and power to produce maximum bio oil yield. Moringa bio oil yield increased from 7.2 wt% at 300°C in 5 minutes to 12.9 wt% at 450°C in 13 minute whereas Karanja bio oil yield increased from 5.7 wt% at 300°C to 10.6 wt% at 450°C in 13 minutes. Bio char of Moringa start to decrease from 63.8 wt% at 300°C to 49.6 wt% at 450°C in 16 minutes whereas bio char of Karanja start to decrease from 64.2 wt% at 300°C to 48.6 wt% at 450°C in 16 minutes. Bio oil of both raw materials showed that the maximum yield when pyrolysis time is 13 minutes in 800 W but after 16 minutes the bio oil yield of Moringa decrease of 2.4% and bio oil yield of Karanja decrease of 4.7%. The calorific value for Moringa oil is 25.08 MJ/kg whereas Karanja oil is 20.36 MJ/kg. A variety of functional groups of alcohol, ketones, aldehydes and carboxylic acid in Moringa oil and Karanja oil was found in FTIR results. The pH value of Moringa oil and Karanja oil are 4.38 and 5.86 respectively. In overall, microwave pyrolysis has potential to produce bio oil as it can narrow energy gap and reduce negative environmental impact.